2006
DOI: 10.1111/j.1525-1438.2006.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase expression in both normal endometrium and endometrial cancer

Abstract: The aim of this study was to investigate the relationship between heparanase expression and prognostic factors in endometrial cancer, as well as the relationship between heparanase expression during phases of the normal endometrial cycle. Immunohistochemical analysis of 166 endometrial cancers and 34 normal endometria in various phases of growth was performed. The heparanase expression in the late-proliferative phase of normal endometria was found to be significantly higher than in either the early-proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This observation was confirmed by the finding that increased expressions of heparanase-1 mRNA and protein correlate with increased heparanase activity and the metastatic capacity of rat and human breast cancer cells [53, 54]. Since then, this correlation has been observed in a variety of human tumour-derived cell lines and tissues, including those of the bladder [119], pancreas [120], cervix [121], colon [122], ovary [123], endometrium [124], prostate [83], thyroid [125], liver [126], oesophagus [110], stomach [109], oral cavity [127], galbladder [128], nasopharynx [129], brain [130], salivary gland [131] and in multiple myeloma [132] and acute myeloid leukaemia [133]. Consistently, as already mentioned above, elevated levels of heparanase-activity have been detected in sera and urine samples of patients suffering from an aggressive metastatic disease [100–102].…”
Section: Involvement Of Human Heparanase-1 In Normal and Pathologicalmentioning
confidence: 88%
“…This observation was confirmed by the finding that increased expressions of heparanase-1 mRNA and protein correlate with increased heparanase activity and the metastatic capacity of rat and human breast cancer cells [53, 54]. Since then, this correlation has been observed in a variety of human tumour-derived cell lines and tissues, including those of the bladder [119], pancreas [120], cervix [121], colon [122], ovary [123], endometrium [124], prostate [83], thyroid [125], liver [126], oesophagus [110], stomach [109], oral cavity [127], galbladder [128], nasopharynx [129], brain [130], salivary gland [131] and in multiple myeloma [132] and acute myeloid leukaemia [133]. Consistently, as already mentioned above, elevated levels of heparanase-activity have been detected in sera and urine samples of patients suffering from an aggressive metastatic disease [100–102].…”
Section: Involvement Of Human Heparanase-1 In Normal and Pathologicalmentioning
confidence: 88%
“…Our results suggest that heparanase expression is upregulated in both atrophic endometrium and SPC, thus supporting a poor prognosis in SPC and possibly implying that atrophic endometrium is, by definition, more prone to carcinogenesis. In contrast, a recent study by Kodama et al [12] showed heparanase expression to be absent. The differences between our study and theirs might be accounted for by the small number of samples tested by both groups.…”
Section: Discussionmentioning
confidence: 77%
“…Increased expression of heparanase has been linked to progressive dysplasia and a worse prognosis in a myriad of cancers [9,10]. Heparanase expression was found to be increased in correlation with clinical stage, tumor grade, lymph node metastasis, and decreased overall survival in endometrial cancer [11,12]. One recent study suggested a possible role for estrogen in inducing heparanase overexpression in breast carcinoma [13].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of HPSE is detected in a wide range of human cancers by immunohistochemistry, in situ hybridization, real‐time PCR analyses and is shown to correlate with metastatic potentials (Barash et al, 2010). In EC, previous studies showed higher HPSE expression in endometrial carcinoma of grade 2 + 3, advanced FIGO stage and carcinoma with deep myometrial invasion, positive lymph node, lymphvascular space involvement (Canaani et al, 2008; Inamine et al, 2008; Hasengaowa et al, 2006). Hasengaowa et al indicated deteriorating prognoses (both disease‐free and overall survival) of 166 EC patients associated with elevated HPSE expression levels (Hasengaowa et al, 2006).…”
Section: Discussionmentioning
confidence: 92%